Inhibisi Korosi Ekstrak Buah Pinang (Areca catechu L.) Sebagai Penghambat Laju Korosi Pada Baja Karbon Rendah C-Mn Steel dengan Medium Korosif HCl dan NaCl - nika khumaidah; Ediman Ginting Suka; Syafriadi Syafriadi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
Corrosion inhibition of areca nut extract (Areca catechu) as the resistor of corrosion rate in low carbon steel with HCl and NaCl corrosive medium concentrated at 3% had been reasearched. The C-Mn steel corrosion rate was examined during a 96 hours of submersion with and without the addition of areca nut extract with the concentration rate at 10%, 15%, and 20% respectively. The examination was done with the weight loss method. The result of the research shows that the use of higher the concentration of areca nut extract resulted in the decrease of corrosion rate and the increase of corrosion inhibition capability. The highest rate of corrosion effectiveness was found in the 20% concentration in both HCl and NaCl with the rate of 86,06% and 85,62% respectively. The result of X-Ray diffraction (XRD) characterization showed that the phase formed was pure Fe. Scanning Electron Microscopy (SEM) characterization showed uneven clusters with smaller size. Holes and cracks were not formed that the corrosion rate was lower compared to the sample without inhibitor addition. The characterization Energy Dispersive Spectroscopy (EDS) in the sample without inhibitor showed the presence of Cl substance.